Visualization of Sacral Nerve Roots via Percutaneous Intraspinal Navigation (PIN) - Fujimoto, Takuya (AJNR Am J Neuroradiol, 2005)
Summary: A percutaneous technique for visualizing sacral nerve roots is described. A fiberscope was inserted into the subarachnoid space through a sheath that was inserted via a percutaneous lumbar puncture. The sacral nerve roots were identified with endoscopic visualization and x-ray fluoroscopy localization of the endoscope. These images were compared with those obtained from a videoscope, which revealed better imaging. Specific sacral nerve roots can be identified by using a combination of endoscopy and x-ray fluoroscopy. This technique may enable minimally invasive interventions such as lysis of adhesions, arachnoid cyst decompression, selective dorsal rhizotomy, and more selective and precise nerve stimulation electrode placement.